"Privacy by Design" implementation: Information system engineers' perspective. (August 2020) - Bu, Fei; Wang, Nengmin; Jiang, Bin; Liang, Huigang
Highlights: Privacy by Design (PbD) implementation process can be understood from a perspective of Intention-to-Behavior. Appropriate incentive mechanism is a critical factor in PbD implementation. Work Impediment is negatively associated with information system engineers' Performance Expectancy regarding PbD usage. Effort Expectancy regarding PbD usage is not a necessary predictor for information system engineer's intention regarding PbD usage. Abstract: In privacy information security literature, Privacy by Design (PbD) is recognized as a positive protection paradigm capable of providing higher privacy protection throughout information products' entire lifetime. It is becoming the dominant privacy protection pattern. Considered to be a promising development tendency towards the information industry, it is garnering interest among researchers and professionals. However, PbD still lacks specific implementation instructions, and it is not popularized among information system engineers. Weighing the pros and cons leads to information system engineers' uncertainty regarding PbD adoption, since existing research on the linkage between PbD implementation and information system engineers' individual factors is inconclusive. Through the lenses of information system engineers, this study aims to advance implementation of PbD by exploring the influence factors of individual and organizational contexts. Real data from 253 practitioners in China's IT industry were used to understand the antecedent of PbD implementation and interaction effects among different dimensions of engineers' adopting behaviors. The findings have demonstrated that appropriate incentive mechanism is a critical factor in PbD implementation by promoting engineer's social influence regarding PbD usage and further affecting both their intentions about adopting PbD and implementing action. This study reveals, for the first time, the role of incentive mechanism in advancing PbD implementation from the information system engineer perspective, and contributes to a deeper understanding of the determinants of PbD adoption by providing a holistic theoretical lens. The findings provide theoretical guidance to IT organizations with guidelines on PbD implementation for higher privacy information protection performance of products.